Implementation of an enrolment planning model at a university of technology - Bleazard, David; Lourens, Amanda (South African Journal of Higher Education, 2016)
This paper provides a brief history of enrolment planning in South African higher education, an overview of the institutional setting of the Cape Peninsula University of Technology (CPUT) as well as the operational context of the company, IDSC, that created an implementable enrolment planning model. The difficulties in projecting detailed enrolment numbers as required by the Department of Higher Education and Training (DHET) and the main issues in terms of the development, deployment and outcome of the enrolment planning model are discussed. We also provide a brief overview of the field of academic analytics and locate the enrolment planning model within it. The usefulness and novelty of the model as an enrolment planning and monitoring tool is outlined in the context of a new approach to higher education funding by DHET that may result in penalties for universities that over- or under-enrol students.